Tackling property damage: a guide for local commerce groups, councils and police - Anthony Morgan
Introduction: Property damage is the intentional ‘destruction or defacement of public, commercial and private property’. This covers a range of different acts, including vandalism (eg smashing windows, knocking over letterboxes) and graffiti. Graffiti is the act of marking property with writing, symbols or graphics and is illegal when committed without the property owner’s consent. According to the Australian Bureau of Statistics’ Crime Victimisation Survey 2011–2012, malicious property damage was more common than any other property offence, with 7.5 percent of respondents reporting having been a victim in the previous 12 months. The cost of property damage to private property owners, local and state governments and businesses are significant, with an estimated cost of $1,522 per incident (in 2012 dollars) and a total cost to the Australian community of nearly $2 billion each year. Using the handbook This handbook forms part of a series of guides developed by the Australian Institute of Criminology (AIC) to support local commerce groups (ie representative groups for business owners and operators), local government and the police to implement evidence-based crime prevention strategies. This handbook has been developed to help guide project managers through the stages of planning, implementing and evaluating a crime prevention project to reduce property damage offences in their local community, particularly in and around commercial precincts. The handbook provides an overview of the three key stages that are involved in delivering a project to reduce property damage: Stage 1: Planning; Stage 2: Implementation; and Stage 3: Review. These steps do not necessarily need to be undertaken in order. Some steps may be undertaken concurrently or it may be necessary to revisit earlier steps. However, it is vital that some steps, such as consulting stakeholders and planning for evaluation, be undertaken early on in the project. Property damage is a very broad offence category. The choice of a particular intervention or interventions will depend largely on the nature of the local problem. Similarly, the successful implementation of a prevention strategy will often be heavily influenced by the characteristics of the local community. This needs to be considered throughout the life of a project